DISTINCTION BETWEEN PENAEUS INDICUS H. MILNE EDWARDS AND PENAEUS MERGUIENSIS DE MAN (CR USTACEA : PENAEIDAE) WITH SPECIAL REFERENCE TO JUVENILES - Muthu, M S; Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Clear-cut differences between the juveniles of PCllaellS illdiclIs and Pellaells merglliâ‚¬lIsis are pointed out in this paper. On the basis of the . colour pattcrn of the antcnnal flagella, antennular flagella and the pJeopods, and the disposition of the rostral teeth it is nOw possible to identify the juveniles of P. illdiclis and P.lIlerglliellsis with certainty.